Comparison of two simulators for individual based models in HIV epidemiology in a population with HSV 2 in Yaoundé (Cameroon) - Hendrickx, Diana M. (2021)
Funding Information: The research conducted by D.M.H. and N.H. in this study was funded by the Fonds Wetenschappelijk Onder-zoek—Vlaanderen (Research Foundation—Flanders; FWO, http://www.fwo.be/en/) (Grant Agreements G0E8416N and G0B2317N). The research done by J.D.S. and A.M.V. in this study has been supported in part by Grants G.0692.14 and G0B2317N, funded by the FWO, Belgium. P.J.K.L. was supported By a PhD Grant of the FWO (1S31916N), and is currently funded via a post-doctoral fellowship (1242021N) of the FWO. WD was supported by a postdoctoral fellowship from FWO (12L5816N). Research done by V.M. in this study has been completed as part of the ELTE Thematic Excellence Programme 2020 supported by the National Research, Development and Innovation Office (TKP2020-IKA-05). The authors gratefully acknowledge support from the FWO Scientific Research Community on Network Statistics for Sexually Transmitted Diseases Epidemiology. The computational resources and services used in this work were provided by the VSC (Flemish Supercomputer Center), funded by the Research Foundation—Flanders (FWO) and the Flemish Government—department EWI. Publisher Copyright: © 2021, The Author(s).